Development of amphotericin b Based organogels against mucocutaneous fungal infections - Kavya Gopalan; Jobin Jose (Universidade de São Paulo, 2020)
Amphotericin B is a broad spectrum antifungal agent used to treat fungal infections. Organogel is a semisolid preparation in which the apolar phase gets immobilized within spaces of the three-dimensional structure. The current study aimed at the formulation and comparative evaluation of sorbitan monostearate organogels and pluronic lecithin organogels (PLO). Different compositions of span 60 based organogels were prepared by varying the concentrations of the span 60 and PLO gels were prepared by varying the concentration of Pluronic F 127. The developed organogels were subjected to various characteristics such as pH, viscosity, spreadability, extrudability, and drug release studies. The optimized formulations were evaluated against Candida albicans and carried out ex vivo release study. The optimized formulation was selected from span 60 based organogels, and pluronic lecithin organogels were S1 and P1, respectively. The optimized formulation (S1) showed effective inhibition against Candida albicans. The skin irritation test was carried out on albino mice for optimized formulations and results showed that no irritation to the skin. Based on the results, organogels prepared by sorbitan monostearate showed better antifungal activity, and also all the formulations were found to be stable and safe throughout the study period.